Review : Glycosaminoglycans (GAGs) versus cancer - Marina, Mohd Sham; Nina Suhaity, Azmi; Mohd Hasbi, Ab. Rahim (Hibiscus Publisher, 2014)
Cancer or tumor is a killer disease that brings mortality worldwide. Extracellular matrix (ECM) constituents involve in the potential growth, invasive and metastasis of the tumor cell through its interaction with cell-surface receptors, growth factors and cytokines. Thus, previous researchers came with a discovery of a potential anticancer compound known as glycosaminoglycans (GAGs). GAG is a polysachharide that plays an important role in physiological and pathological conditions by affecting the cell properties and its functions. GAGs are majored from chondroitin sulfate (CS), dermatan sulfate (DS), keratan sulfate, heparin and heparan sulfate (HS), and hyaluronan which have their own important roles in cancer progression and cell signalling. Many researchers have reported the finding of GAGs in animal but there were least research of GAGs extraction from seafood and marine fauna. There are a few researches on extraction and analysis of GAGs from seafood wastes and marine lives such as white shrimp heads, mollusks and cuttlefish that showed the potential of GAGs as anticancer. Therefore, more researches on extraction of GAGs from seafoods need to be carried out as it can be anticancer therapeutic approaches for future prospective.